Native Pitcherplants of Florida - Megan E. Brown; Debbie L. Miller (EDIS)
Pitcherplants are perennial plants with groups of leaves modified into traps or pitchers. They have tubular leaves with lids or hoods at the top that secrete nectar to attract prey. Once insects are on the lip of the pitcher, they can slip on the waxy opening and fall into the plant. This 5-page fact sheet provides descriptions of the ranges, appearance, and flowering of the six pitcherplant species native to Florida. Written by Megan E. Brown and Debbie L. Miller and published by the UF Department of Wildlife Ecology and Conservation, January 2013.